Substance Abuse, Violence, and HIV/AIDS (SAVA) Syndemic Effects on Viral Suppression Among HIV Positive Women of Color - Sullivan, Kristen A. (AIDS Patient Care STDS, 2015)
The combined epidemics of substance abuse, violence, and HIV/AIDS, known as the SAVA syndemic, contribute to the disproportionate burden of disease among people of color in the US. To examine the association between HIV viral load suppression and SAVA syndemic variables, we used baseline data from 563 HIV+ women of color treated at nine HIV medical and ancillary care sites participating in HRSA's Special Project of National Significance Women of Color (WOC) Initiative. Just under half the women (n=260) were virally suppressed. Five psychosocial factors contributing to the SAVA syndemic were examined in this study: substance abuse, binge drinking, intimate partner violence, poor mental health, and sexual risk taking. Associations among the psychosocial factors were assessed and clustering confirmed. A SAVA score was created by summing the dichotomous (present/absent) psychosocial measures. Using generalized estimating equation (GEE) models to account for site-level clustering and individual-covariates, a higher SAVA score (0 to 5) was associated with reduced viral suppression; OR (adjusted)=0.81, 95% CI: 0.66, 0.99. The syndemic approach represents a viable framework for understanding viral suppression among HIV positive WOC, and suggests the need for comprehensive interventions that address the social/environmental contexts of patients' lives.